EFISIENSI DAN PRODUKTIVITAS ORGANISASI PENGELOLA ZAKAT NASIONAL - Nurul Ichsan; Nakania Yumena (IZZI: Jurnal Ekonomi Islam, 2022)
This study aims to analyze the level of efficiency and productivity of the National Zakat Management Organization during the periode 2015 – 2018 using Data Envelopment Analysis and Malmquist Productivity Index in the first stage. The second stage tests the factors that influence the level of efficiency using the Tobit Regression Model. The object of research is the financial statements at BAZNAS, LAZ Al Azhar, and Rumah Zakat. The DEA calculation results show that on average the three OPZ produce a100% efficiency level. However, only Rumah Zakat produced less than 100% optimal efficiency levels in 2015. In the calculation of productivity, on average the total productivity factor was driven by technological change, the change in efficiency resulted in a valeu of 1.000 so that it had no effect on the TFP. Furthermore, in the second stage of processing the Tobit Regression Model shows that fixed assets and current assets have a positive and significant effect on efficiency and operational costs have a negative and significant effect on the level of efficiency. Meanwhile, funds raised, personnel costs, and channeled have no significant effect on the level of efficiency.